PERENCANAAN ALAT PENUKAR KALOR SHELL DAN TUBE PROSES PENYERAPAN RESIDU DAN PELEPASAN UAP DENGAN KAPASITAS 2.550.000 BTU/JAM - Jumianto Jumianto (Fakultas Teknik dan Ilmu Komputer, 2022)
A heat exchanger is a device in which heat is transferred from a high-temperature fluid to a low-temperature fluid. Where the heat exchange that occurs in two types of different temperatures are not in contact, namely the heat transfer fields which are generally in the form of pipe walls or fins mounted on the pipe (fin) so that the two fluids will reach the same final temperature in the amount of heat. The displacement is estimated by equating the losses from the hotter fluid energy with obtaining a lower fluid energy, which is used for heat exchange in the form of the product itself, namely: water, water vapor, ordinary air, flame, residual gas, combustion and so on. In general, this heat exchanger is widely used for chemical engineering processes, power generation, petroleum refining, refrigeration, the food industry and so on. In this case, shell and tube types of heat exchangers are fed by two different types of fluids. Where the residual fluid flows inside the tube (the fluid to be heated), while the vapor fluid flows inside the shell but outside the tube (the fluid that heats the residue).